2010
DOI: 10.1289/ehp.0901584
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Perfluorooctanoic Acid (PFOA) and Thyroid Disease in the U.S. National Health and Nutrition Examination Survey

Abstract: BackgroundPerfluorooctanoic acid (PFOA, also known as C8) and perfluorooctane sulfonate (PFOS) are stable compounds with many industrial and consumer uses. Their persistence in the environment plus toxicity in animal models has raised concern over low-level chronic exposure effects on human health.ObjectivesWe estimated associations between serum PFOA and PFOS concentrations and thyroid disease prevalence in representative samples of the U.S. general population.MethodsAnalyses of PFOA/PFOS versus disease statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
298
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(311 citation statements)
references
References 48 publications
8
298
4
1
Order By: Relevance
“…Several large-scale surveys of Nunavik permanent residents (Dallaire et al 2009), US. general adult population (Melzer et al 2010), and children living near a chemical plant of USA (Lopez-Espinosa et al 2012) suggested the association of increased serum PFCs with abnormal THs levels and thyroid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several large-scale surveys of Nunavik permanent residents (Dallaire et al 2009), US. general adult population (Melzer et al 2010), and children living near a chemical plant of USA (Lopez-Espinosa et al 2012) suggested the association of increased serum PFCs with abnormal THs levels and thyroid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Serum thyroxine (T4) and triiodothyronine (T3) were reduced by PFCs in animal studies [18,19]. A recent study on the general adult population in the United States has suggested that higher concentrations of serum PFOS are associated with thyroid disease [20]. Therefore, further characterization of the endocrine-disrupting effects of PFCs is required for assessing potential health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Human biomonitoring of the general population in various countries (Calafat et al, 2006;Kannan et al, 2004;Metzer et al, 2010). has shown that, in addition to the near ubiquitous presence of PFOS and PFOA in blood, these may also be present in breast milk, liver, seminal fluid, and umbilical cord blood (Lau et al, 2007).…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 99%
“…Modest associations between PFOA and THs (negative for free T4 and positive for T3) were reported in 506 PFOA production workers across three production facilities (Olsen & Zobel, 2007); there were no associations between TSH or T4 and PFOA, and the free TH levels were within the normal reference range. On the other hand, Metzer et al (Metzer et al, 2010) recently determined whether increased serum PFOA or PFOS concentrations are associated with thyroid disease in a general adult US population sample (n = 3,974 individuals ≥ 20 years of age from NHANES waves 1999-2000 (n = 1,040), 2003-2004 (n = 1,454), and 2005-2006 (n = 1,480)). They found that, across all the available data from NHANES, thyroid disease associations with serum PFOA concentrations are present in women and are strongest for those currently being treated for thyroid disease (P=0.002) (Metzer et al, 2010).…”
Section: Perfluoroalkyl Acidsmentioning
confidence: 99%